Light Scalars in Composite Higgs Models - Cacciapaglia, Giacomo; Ferretti, Gabriele; Flacke, Thomas; Serôdio, Hugo (Frontiers in Physics, 2019)
A composite Higgs boson is likely to be accompanied by additional light states generated by the same dynamics. This expectation is substantiated when realising the composite Higgs mechanism by an underlying gauge theory. We review the dynamics of such objects, which may well be the first sign of compositeness at colliders. We also update our previous analysis of the bounds from LHC searches to the latest results, and discuss the projected reach of the High-Luminosity run.